Glia in Pathological Pain: A Role for Fractalkine - Milligan, E. D. (2008)
Microglia and/or astrocytes play a significant role in the creation and maintenance of exaggerated pain states with inflammatory and/or neuropathic etiologies. The chemokine, fractalkine, has several functions, including the newly recognized role of mediating neuropathic pain conditions. Although constitutively expressed and released during inflammation, increased release of fractalkine binds to and activates microglia glia leading to pathological pain. We review the critical role of fractalkine in neuron-to-glial communication after peripheral nerve injury and inflammation and explore anti-inflammatory cytokines like interleukin-10 as a novel and effective approach for clinical pain control.